What Is Distinctive about the Sexual Victimization of Female Adolescents? A Comparison with the Sexual Victimization of Children and Adults - Paquette, Sarah (Victims & offenders, 2023)
This study examines the characteristics of the sexual victimization of adolescents and provides a comparison with the ones of children and adults. The sample includes 2,665 sexual abuse cases of female children, adolescents, and adults in France. Analyses revealed differential patterns in factors associated with the sexual victimization of adolescents. Findings suggest that the sexual victimization of adolescents may be located along a continuum in terms of sexuality, antisociality, and situational factors, between children and adult victimization. Implications for the prevention of the victimization of adolescents, clinical considerations for offenders, and avenues for future research are discussed.